Mastering Microsoft Visual Web Developer 2005 express edition - Mueller, John Paul (Wiley, 2006)
This Mastering book from Sybex, offers beginning through advanced instruction, with emphasis on beginner and intermediate topics. Built around practical applications, you'll learn how to create feedback forms, develop a site search, build a shopping cart, use pop-ups and redirection, and much more.